Los retos lingüísticos de Venezuela: desafíos internos y globales - Bolívar, Adriana (Diálogos Latinoamericanos, 2009)
In this paper two types of linguistic challenges faced by Venezuela are examined: the internal situation with respect to mother tongues, and how national universities have approached international relations through the teaching of foreign languages. It is argued that, although the new Constitution of 1999 recognizes indigenous languages as official, in practice Spanish remains the only official language. It is shown that the responsibility of foreign language teaching has been in the hands of state and private universities that have taken the lead and decided on the policies to follow, although the Ministry of Education keeps control of the teaching profession. It is concluded that the preservation of minority languages is a complex matter that includes improving the life conditions of minority groups and taking real actions against discrimination. As for foreign languages, it is suggested that universities should join efforts in order to reinforce national as well as international dialogue.